Pengaruh Pengendalian Internal dan Good Corporate Governance Terhadap Pencegahan Kecurangan (Fraud) - Fitriana Fitriana; Rahmat Agus Santoso; Nanang Rustandi; Sudharmawan Sudharmawan (CV. Ulil Albab Corp, 2024)
Research on the influence of internal control and good corporate governance on fraud prevention aims to find out and review previous research related to internal control variables, good corporate governance for preventing financial fraud. This research uses a qualitative method with a literature review approach to strengthen arguments with information collected in articles published in the accredited national journal Sinta. This research found that based on previous research mapping, many have proven that internal control and good corporate governance have a positive effect on fraud prevention, with the effectiveness of the internal control system helping to reduce opportunities, pressure and rationalization of fraudulent acts.